2003
DOI: 10.1016/s0969-8051(02)00350-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3-[125I]iodo-α-methyl-L-tyrosine transport via human L-type amino acid transporter 1

Abstract: We examined transport of 3-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
(47 reference statements)
1
37
0
Order By: Relevance
“…Consistent with this, we previously showed that a-methyl phenylalanine and a-methyl 3,4-dihydroxyphenylalanine and AMT inhibited L-14 C-leucine uptake mediated by LAT1, but they had less of an effect on LAT2 (22,24,25). Moreover, in the amphibian oocyte expression system, we observed that L-3-125 I-a-methyl tyrosine ( 125 I-IMT) is transported by LAT1 but not by LAT2 (27).…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with this, we previously showed that a-methyl phenylalanine and a-methyl 3,4-dihydroxyphenylalanine and AMT inhibited L-14 C-leucine uptake mediated by LAT1, but they had less of an effect on LAT2 (22,24,25). Moreover, in the amphibian oocyte expression system, we observed that L-3-125 I-a-methyl tyrosine ( 125 I-IMT) is transported by LAT1 but not by LAT2 (27).…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that in cultured human glioma cells, membrane transport of IMT is dominated by BCH-sensitive transport system, LAT1. 20,21 LAT1-mediated IMT transport and 4F2 antigen expression are dependent on proliferation rate of human glioma cells in vitro and are significantly correlated to each other. 20 These data give further support to the involvement of the LAT1 in cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to LAT3 (15), L-leucinol and L-valinol, which have a hydroxymethyl group instead of a ␣-carboxyl group, also inhibit the uptake of L-phenylalanine. Methyltyrosine, a LAT1-specific inhibitor (27), is a poor inhibitor of LAT4 (Fig. 4a).…”
Section: Identification Of Lat4 -Lat3mentioning
confidence: 99%